Environmental Health Risk Analysis of Copper Exposure to Catfish Commonly Consumed By People in Ulak Jermun Village, Ogan Komering Ilir (Jurnal Ilmu Kesehatan Masyarakat, 2022)
Catfish cultivated in rivers can be contaminated by heavy metals such as copper (Cu) which come from activities around the river. Copper exposure through the consumption of catfish will be harmful to health. This research aim to   analyze the public health risks due to catfish consumption in Ulak Jermun Village, Ogan Komering Ilir. The design of study was cross sectional using the Environmental Health Risk Analysis method. The research respondents were 113 people with 5 samples of catfish taken from the river where the fish were cultivated. The analysis of heavy metal copper using the Atomic Absorption Spectrophotometer (AAS) method. The results showed copper contamination in catfish with an average concentration of 1.67 mg/kg. There were no respondents with RQ value > 1 for realtime non-carcinogenic health risks, but 11 people (9.7%) of respondents with RQ value > 1 for non-carcinogenic health risks in a lifetime. Meanwhile, for realtime carcinogenic exposure 34.5% had ECR values > 10-4 and 100% of respondents had ECR values > 10-4 for carcinogenic effects in lifetime. The conclusion was the people of Ulak Jermun are at risk of experiencing carcinogenic diseases due to copper exposure with the largest percentage of people aged> 32 years, female, and weighing ≤ 57 kg.